3x-x-3-1-3-dx- Tinku Tara March 15, 2024 Integration 0 Comments FacebookTweetPin Question Number 205294 by depressiveshrek last updated on 15/Mar/24 ∫3x−x33dx Answered by Frix last updated on 15/Mar/24 ∫(3x−x3)13dx=t=x2332∫t−13(1−t)13dt==32t232F1(−13,23;53;t)==3x4322F1(−13,23;53;x23)+C Terms of Service Privacy Policy Contact: info@tinkutara.com FacebookTweetPin Post navigation Previous Previous post: Question-205306Next Next post: Question-205319 Leave a Reply Cancel replyYour email address will not be published. Required fields are marked *Comment * Name * Save my name, email, and website in this browser for the next time I comment.